Pedagogical conditions required in current university teaching (Revista Electrónica Calidad en la Educación Superior, 2023)
University teaching entails a relevant social responsibility for the development of a country, since it contributes to the training of professionals in different areas of knowledge, which should then be incorporated into the world of work. The topic is of interest as long as there is a large number of university teachers without pedagogical training to play a relevant role in the teaching and learning process. The main objective of this article is an analysis of the pedagogical conditions required for higher education. Among the main conclusions, is determinated the importance of the development of basic conditions in the person who assumes the function of university teaching, which revolve around pedagogical training as the dynamizer axis of learning environments that has repercussions on the relational links and the academic performance of the students.
Keywords: Higher education; university teaching; pedagogy; learning process